Isolation, detection and characterization of swine hepatitis E virus from herds in Costa Rica - Kase, Julie (2008)
Although swine HEV isolates from North America, Europe, and Asia have been genetically characterized, little is known about the strains presumed to be circulating in Latin America. In this study, seven commercial swine production sites in Costa Rica were surveyed for HEV. Using RT-PCR, with primers located in ORF2, 19/52 fecal samples produced a product of the expected size following two rounds of amplification. Most positive samples were from swine between the ages of 1.5 and 4 months. This study provides documented evidence for the endemicity of HE infections in swine residing in Central America. Through nucleic acid sequencing, isolates were found to be genetically similar, if not identical, with no amino acid substitutions. By comparison of swine and human HEV strains representing all four genotypes and phylogenetic analysis, our isolates closely resembled the US swine and human and other Genotype III strains, with 85–93% nucleic acid identity.